Monkeypox – An emerging pandemic. (2022) - Ajmera, Kunal M.; Goyal, Lokesh; Pandit, Trupti; Pandit, Ramesh
Abstract: Monkeypox–a zoonotic disease caused by the monkeypox virus, an orthopoxviruses family member. Recently monkeypox cases are increasing at an alarming rate in the US and worldwide. Health care professionals should keep a high index of suspicion for the disease in anyone with new onset fever, a vesicular or pustular rash with central umbilication, and lymphadenopathy. Such patients should be isolated at home or the hospital to prevent secondary transmission. The cases are typically self-limited, and most people only need home supportive care. However, as recommended by CDC, immunocompromised patients, pregnant patients, and children younger than eight years should be offered pre- or post-exposure prophylaxis with vaccines. The current outbreak explicitly targets a cohort of homosexual and gay patients. The role of sexual transmission of the virus needs to be explored further. Patients with severe symptoms or respiratory complications can also be treated with antivirals such as tecovirimat (TPOXX) and brincidofovir or with intravenous vaccinia immune globulin (VIGIV).